Comparison Between Ultrasound Imaging and Mammogram Based on the Influence of Filter Materials on the Quality of Digital X Mammography - Fathya Shabek (African Journal of Advanced Pure and Applied Sciences, 2023)
Diagnosis of cancer with the regular mammogram may be unreliable in nevertheless many cases since this mammogram may be unable to detect early tumors in many mammary glands. Digital mammogram is a modern technique that attempts to increase the accuracy of tumor detection. It can also be added to the magnetic resonance imaging. The digital mammogram can depict tumors in the mammary glands, which involve injection of intravenous dye while the patient is photographed with a series of mammography images that shows the flow of dye over time. It is based on the principle that fast-growing tumor’s need to increase the supply of blood to support their growth. The formula accumulates in such regions, so the digital mammogram provides therefore, a method of imaging based on the distribution of dye in the breast tissue, but it is still a two-dimensional technique. Although breast magnetic resonance imaging (MRI) may be used as an additional method to digital mammography in patients with high density mammary glands or non- homogenous tissue with ultrasound waves or both, and preoperative screening for women with breast cancer, it looks like the routine use of breast magnetic resonance imaging is unnecessary.